Proposal of Artifact for Motivational Analysis of Job Characteristics - De Sordi, José Osvaldo; Azevedo, Marcia Carvalho (Review of Business Management, 2013)
The theory for studying the motivational potential of certain jobs – or job design – was developed for the context of an industrial society, one that is quite different from our current information society. This research proposes a device for discussing and analyzing the key characteristics of motivation referring to jobs, according to the theories of job design and to the information society context. This is a pragmatic research, which applies the Design Science research strategy. Based on an inventory and on content analysis of scientific research concerning job design – published in the twenty-first century in the electronic databases of PROQUEST and EBSCO scientific articles – the motivational characteristics that are associated to this theory were identified, structured and presented in the proposed device.